The Use of Adobe Flex in Combination with Java EE Technology on the Example of Ticket Booking System - Juszkiewicz, P.; Sakowicz, B.; Mazur, P.; Napieralski, A. (ХНУРЭ, 2011)
The article presents the possibility of building Rich Internet Applications using Flex technology as well as a method of connecting them with Java EE applications based on a Spring framework. As an example, a ticket booking system was created. The most important issues related to rich internet applications and possibilities of used technologies were shown basing on this system. The application was elaborated owning to usage of the latest open-source technologies.
Keywords: BlazeDS; PureMVC; Flex; Rich Internet Application